Microarrays: a new era in development of oncohematology - Ye. A. Nikitin; A. B. Sudarikov; A. V. Baranova (Онкогематология)
Introduction of the immunophenotyping in 70-ties and 80-ties of the past century has led to significant revision of conception of hematological malignancies. A new era in developement of medicine and oncology in particular is related to functional genomics. This field of molecular biology attempts to make use of the vast wealth of data produced by genomic projects for studying gene functions and interactions. Functional genomics focus on the dynamic aspects such as gene transcription, mRNA translation, and protein-protein interactions, as opposed to the static aspects of the genomic information such as DNA sequence or structure. Several genomic technologies have been developed to study gene expression. Gene expression profiling on DNA microarrays has been particularly useful in analyzing expression of thousands genes in parallel. Modern microarrays contain comprehensive probe sets which are able to measure the majority of genes encoded in human genome. Here we focus on microarray technology, discuss its clinical applications and briefly review some results obtained by this method in researches of hematological malignancies.